TRANSPARANSI DAN AKUNTABILITAS DALAM LAPORAN KEUANGAN SYARIAH : TINJAUAN SISTEMATIS - niken, Niken Ardelia Zamrizal; Izzah Sholehah; Azzah Nabila (Journal of Islamic Economics and Finance, 2025)
This study examines the application of the concept of transparency and accountability in the preparation of financial statements based on Sharia principles. Its main focus is to identify the characteristics of Sharia financial statements and their impact on the achievement of transparency and accountability. Furthermore, this study analyzes Islamic Financial Entities that face common challenges ini order to uphold principles. Using a systematic review approach, this study analyzes the literature and current practices in Islamic finance. This research shows that fairness and ethical principles are inherent in Sharia financial reporting. Islamic financial reporting is an important trust-building mechanism based on transparency and accountability. However, challenges such as the lack of uniform standardization and limited stakeholder understanding present significant obstacles. This research shows that regulations must be enforced and education must be increased to support the improvement of the quality of Islamic financial statements.